Maghrebi-French Directors Behind the Camera: The Cinema of the Second G - Dina Sherzer (Studies in 20th & 21st Century Literature, 2002)
In an article entitled "De Nanterre à Hollywood" ("From Nanterre to Hollywood"), published in a 1996 issue of L'Express, Dalila Kerkouche writes: "leur père tenait le marteau piqueur, eux manient la caméra…
Keywords: De Nanterre à Hollywood; From Nanterre to Hollywood; 1996; L' Express; Dalila Kerkouche; Maghrebi-French Directors; Cinema; Film